Neoadjuvant chemotherapy for primary cutaneous/soft tissue angiosarcoma: Determining tumor behavior prior to surgical resection. Issue 7 (13th March 2015) - Oxenberg, Jacqueline; Khushalani, Nikhil I.; Salerno, Kilian E.; Attwood, Kristopher; Kane, John M.
Abstract : Background: Given the propensity for hematogenous metastases, neoadjuvant chemotherapy (NAC) could treat occult metastatic disease early, potentially improving survival and better defining which primary angiosarcomas (AS) benefit from surgical resection. Methods: A retrospective comparison was performed of 23 patients with resectable, localized cutaneous/soft tissue primary AS treated with surgery alone (S, n = 13) or NAC followed by surgery (NAC‐S, n = 12). Results: Primary sites included breast/chest (n = 9), head/neck (n = 9), extremity (n = 3), and other (n = 2). 23% S versus 40% NAC‐S had prior radiation (RT). NAC regimens were paclitaxel (n = 6) or gemcitabine/docetaxel (n = 4). Seventy percent were high grade. Distant metastases were found in 17% after NAC. Non‐primary wound closure was required in 54 %S versus 30%NAC‐S ( P  = 0.4). R0 resections were achieved in 85% S versus 80% NAC‐S (30% had a complete pathologic response). Two‐year local recurrence (LR)‐free, disease‐free, and overall survivals were 67.1, 38.5, and 61.5% for S versus 68.6, 54.9, and 68.6% for NAC‐S ( P  = 0.52, 0.67, and 0.58). The mean number of surgical resections/patient to maintain local control was 1.8 S versus 1.3 NAC‐S ( P  = 0.06). Conclusions: NAC for primary AS was well tolerated. Although there was no statistically significant survival benefit, NAC helped define who would benefit from surgical resection. J. Surg. Oncol. 2015 111:829–833 . © 2014 Wiley Periodicals, Inc.